2020
DOI: 10.1007/s00220-020-03696-2
|View full text |Cite
|
Sign up to set email alerts
|

Effective Behaviour of Critical-Contrast PDEs: Micro-resonances, Frequency Conversion, and Time Dispersive Properties. I

Abstract: A novel approach to critical-contrast homogenisation for periodic PDEs is proposed, via an explicit asymptotic analysis of Dirichlet-to-Neumann operators. Norm-resolvent asymptotics for non-uniformly elliptic problems with highly oscillating coefficients are explicitly constructed. An essential feature of the new technique is that it relates homogenisation limits to a class of time-dispersive media.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 90 publications
(324 reference statements)
0
60
0
Order By: Relevance
“…An overview of the existing approaches to obtaining operator-norm estimates would not be complete without mentioning also the works [41,42,44] that use, respectively, the method of periodic unfolding and the analysis of boundary integral representations, as well as the paper [70] cited above, based on the analysis of the homogenisation corrector via "Steklov smoothing", and the recent papers [26,27], which employ an analysis of appropriate Dirichletto-Neumann (or Poincaré-Steklov) operators. The methods of these works could also be considered in the context of thin and singular structures, however we refrain from pursuing the related discussion here.…”
Section: Introductionmentioning
confidence: 99%
“…An overview of the existing approaches to obtaining operator-norm estimates would not be complete without mentioning also the works [41,42,44] that use, respectively, the method of periodic unfolding and the analysis of boundary integral representations, as well as the paper [70] cited above, based on the analysis of the homogenisation corrector via "Steklov smoothing", and the recent papers [26,27], which employ an analysis of appropriate Dirichletto-Neumann (or Poincaré-Steklov) operators. The methods of these works could also be considered in the context of thin and singular structures, however we refrain from pursuing the related discussion here.…”
Section: Introductionmentioning
confidence: 99%
“…In our analysis of BVP, we adopt the approach to the operator‐theoretic treatment of BVP suggested by [53], which appears to be particularly convenient for obtaining sharp quantitative information about scattering properties of the medium, cf. , for example, [17], where this same approach is used as a framework for the asymptotic analysis of homogenisation problems in resonant composites.…”
Section: Introductionmentioning
confidence: 99%
“…The present paper is a development of the recent activity [16][17][18][19] aimed at implementing the above strategy in the context of problems of materials science and wave propagation in inhomogeneous media. Our recent papers [20,21] have shown that the language of boundary triples is particularly fitting for direct and inverse scattering problems on quantum graphs, as one of the key challenges to their analysis stems from the presence of interfaces through which energy exchange between different components of the medium takes place.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interesting results on the norm-resolvent asymptotics in high-contrast homogenisation are obtained in [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%